DIMENSIONS OF GERMAN CULTURE IN ITAPIRANGA (SC): THE IMMEDIATE HERITAGE AND ITS RELATION TO IDENTITY, MEMORY AND TRADITION - Orestess Franzen, Douglas; Machado Badalotti, Claudine; Carpes de Chaves, Gabriel (Revista de Historia Social y de las Mentalidades, 2019)
The article analyzes the relationship of intangible heritage in Itapiranga (SC) with the practice of identity, memory and tradition, through its dimension with Germanic culture. The objective is to make an analysis of the local historical formation relating germanity with the cultural practices perceptible in the society. From this it is intended to collaborate in the debate about the potentialities of intangible heritage as a value of culture and its symbolic dimensions.
Keywords: Itaparinga; Patrimony; Memory